Compliance to hand hygiene and its associated factors among health care provider in general hospital in Addis Ababa, Ethiopia - Ziyad Ahmed Abdo; Meaza Gezu Shentema; Mulugeta Tamire Awono; Yohannes Lakew Tefera (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Globally, a significant proportion of healthcare providers and patients acquire nosocomial infections through contaminated hand. Failure to perform appropriate hand hygiene is considered to be the leading cause of healthcare-acquired infection worldwide. OBJECTIVES: To describe compliance to hand hygiene and its associated factors among healthcare provider in general hospital in Addis Ababa, Ethiopia. METHODOLOGY: An institutional based cross-sectional study was conducted among healthcare providers working in general hospitals in Addis Ababa. Multistage sampling system was used to select 708 participants. Data were collected using a self-administered structured questionnaire. Data were entered into Epi data version 3.1, and then exported to SPSS version 22 for data management and analysis. Multivariable logistic regression was performed to identify factors associated with healthcare providers hand hygiene practice. RESULTS: A total of 651 healthcare providers were participated in this study, with a response rate of 91.9%. The overall good hand hygiene practice of healthcare providers were 50.4%. Educational status: master and above holders (adjusted odds ratio [AOR] [95% of confidence interval (CI)]) = 0.46 (0.26, 0.84) and first-degree holders (AOR [95% of CI]) = 0.43 (0.23, 0.82), attitude (AOR [95% of CI] = 1.61 (1.09, 2.38), knowing functionality of infection prevention committee (AOR [95% CI]) = 1.57 (1.03, 2.38), functionality of hand washing sink (AOR [95% of CI]) = 2.26 (1.07, 4.79), availability of running water (AOR [95% of CI]) = 1.86 (1.011, 3.432), and availability of hand hygiene guide (AOR [95% of CI]) = 1.66 (1.13, 2.43) were significantly associated with hand hygiene practice. CONCLUSIONS: According to this study, good hand hygiene practice is low. This indicates that patients and healthcare providers are at high risk of acquiring nosocomial infection. Hence, government and management of the hospital must give emphasis on patient safety.